Loss of C1q alters the auditory brainstem response - Chokr, Sima M.; Bui-Tran, Ashley; Cramer, Karina S. (Frontiers in Cellular Neuroscience, 2024)
Neural circuits in the auditory brainstem compute interaural time and intensity differences used to determine the locations of sound sources. These circuits display features that are specialized for these functions. The projection from the ventral cochlear nucleus (VCN) to the medial nucleus of the trapezoid (MNTB) body travels along highly myelinated fibers and terminates in the calyx of Held. This monoinnervating synapse emerges during development as multiple inputs are eliminated. We previously demonstrated that elimination of microglia with a colony stimulating factor-1 inhibitor results in impaired synaptic pruning so that multiple calyceal terminals reside on principal cells of MNTB. This inhibitor also resulted in impaired auditory brainstem responses (ABRs), with elevated thresholds and increased peak latencies. Loss of the microglial fractalkine receptor, CX3CR1, decreased peak latencies in the ABR. The mechanisms underlying these effects are not known. One prominent microglial signaling pathway involved in synaptic pruning and plasticity during development and aging is the C1q-initiated compliment cascade. The role of C1q in the development of the sound source localization pathway was not defined. Here we investigated the classical complement pathway initiator, C1q, in auditory brainstem maturation. We found that C1q expression is detected in the MNTB by the first postnatal week. C1q levels increased with age and were detected within microglia and surrounding the soma of MNTB principal neurons. Loss of C1q did not affect microglia-dependent calyceal pruning. Excitatory and inhibitory synaptic markers in the MNTB and LSO were not altered with C1q knockout. ABRs showed that C1q KO mice had normal hearing thresholds but shortened peak latencies. Altogether this study uncovers the developmental time frame of C1q expression in the sound localization pathway and shows a subtle functional consequence of C1q knockdown.